Analisis Faktor-Faktor Yang Mempengaruhi Produksi dan Pendapatan Usaha Budidaya Ikan Kerapu Cantang Di Kabupaten Lamongan - Sa’adah, Wachidatus; Suyoto, Suyoto (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The purpose of this study is to analyze the production components that affect production and determine the income of the Cantang Grouper aquaculture business. This quantitative research uses a descriptive and analytical approach. To ensure that every member of the population has an equal chance to be selected as a sample, 10 (ten) respondents were selected using a simple random sample. The primary data used came from interviews and questionnaires, in addition to secondary data obtained from various literature and journals related to the research. According to the results of the data analysis carried out, land, labor, and feed are components that affect production and fulfillment of production functions.  With income ranging from Rp. 91.461.000,- per harvest cycle, or Rp. 7.621.750,- per month, Cantang Grouper is a profitable aquaculture business with an R/C ratio of 2.01.